PERANAN ZINC PADA PENANGANAN KASUS PENYAKIT DIARE YANG DIALAMI BAYI MAUPUN BALITA - Riskiyah, Riskiyah (Journal of Islamic Medicine, 2017)
In Indonesia, diarrhea still is one of top problem public health for causing morbidity andÂ  many deaths. All age groups can be attacked by diarrhea, but severe disease with high mortality especially in infants and toddlers. WHO and UNICEF recommend about management of diarrhea in children namely by adding a supplementation of zinc (Zn) on oral rehydration therapy. Zinc functions in the immune system as a second messenger in signal transduction, cell immunity and nutritional immunity. Zinc also plays an important role in reducing the risk and severity of diarrhea. From some research shows that the effects of therapeutic zinc supplementation can reduce the duration of diarrhea, stool output and stool frequency. The supplementation of 20 mg of zinc per day on the eradication of child diarrhea are less than 5 years and 10 mg per day for infants less than 6 months for 10-14 days. The beneficial effects of zinc supplementation in diarrhea that can speed up the regeneration of the epithelium lining the intestine, increasing the absorption of water and electrolytes in the intestine, increase enzyme levels enterocyte brush-border, and enhance the immune response that can speed up clearance of pathogens from the gut.